Theory Creation, Modification, and Testing: An Information Processing Model and Theory of the Anticipated and Unanticipated Consequences of Research and Development - Perla, Rocco J.; Carifio, James M. (Journal of MultiDisciplinary Evaluation, 2011)
Background: Extending Merton’s (1936) work on the consequences of purposive social action, the model, theory and taxonomy outlined here incorporates and formalizes both anticipated and unanticipated research findings in a unified theoretical framework. The model of anticipated research findings was developed initially by Carifio (1975, 1977) and was followed by the addition of the unanticipated findings component by Perla (2006). This is the first formal model, theory and synthesis of anticipated and unanticipated research findings developed to date. The wide-ranging consequences and implications of the model are discussed. Purpose: To the extent that educational researchers, philosophers and scholars reduce unanticipated findings solely to chance, whimsy, or inspiration they declare these occurrences impossible to effectively predict, model or understand. This article provides a way to conceptualize and formally model anticipated and unanticipated research findings. Many concrete examples from the history of science and research and evaluation methodology are provided to illustrate the model as well as various details of an application of the model in developing instructional materials. Setting: Nature of science instructional materials development effort. Intervention: Not applicable. Research Design: Theory and model development using quantitative and qualitative methods including literature review and original model evaluations. Data Collection and Analysis: Content analysis and modified Q-sorts of research related documents, journals, logs, literature and emails as well as various theory construction and modification techniques. Findings: This article demonstrates that a formal model and theory of anticipated and unanticipated research findings can be developed and that such models should inform a broad range of research and evaluation efforts that are conducted daily worldwide. Nine key research and evaluation principles were derived to supplement the formal model and its operations that should be helpful to novice as well as experienced researchers regardless of the research methodology or strategies they are employing.